Preparation and Characteristics Study of ZnS Thin Films by Chemical Bath Deposition Method (Journal of the College of Basic Education, 2022)
Thin films of zinc sulfide (ZnS) have been deposited by chemical bath deposition technique using the zinc nitrate salt(Zn(NO3)2) was used as a source of zinc ions(Zn+2) and thiourea (SC(NH2)2) as a source of negative sulphide ions(S-2). The effect deposition temperature on the structural and optical properties is described. The XRD studies revealed that the deposited films have a polycrystalline and the hexagonal structure and the grain size increases from 22 nm to 45 nm with increasing deposition temperatures. The average transmittance of ZnS films in the visible region was between 40–701% with direct optical energy decreases from 3.66eV to 3.38 eV with increasing deposition temperature.